2018
DOI: 10.1016/j.avb.2018.09.002
|View full text |Cite
|
Sign up to set email alerts
|

The association between attachment and psychopathic traits

Abstract: UvA-DARE (Digital Academic Repository) The association between attachment and psychopathic traits

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 115 publications
(159 reference statements)
0
11
0
Order By: Relevance
“…Based on trauma theory, childhood is a period where secure parental attachment is developed, and as prosocial traits develop from a secure attachment with parents (Grusec & Davido, 2010; Taylor et al, 2013), a traumatic experience of maternal incarceration may impact the child’s security, disrupting the development of attachment toward others. Indeed, psychopathy, particularly the affective features, is linked to maladaptive attachment styles and poor parental bonding (Craig et al, 2013; Gao et al, 2010; van der Zouwen et al, 2018). Research has demonstrated that maternal warmth may interrupt the development of affective psychopathic traits in youth (Kimonis et al, 2013; Waller et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Based on trauma theory, childhood is a period where secure parental attachment is developed, and as prosocial traits develop from a secure attachment with parents (Grusec & Davido, 2010; Taylor et al, 2013), a traumatic experience of maternal incarceration may impact the child’s security, disrupting the development of attachment toward others. Indeed, psychopathy, particularly the affective features, is linked to maladaptive attachment styles and poor parental bonding (Craig et al, 2013; Gao et al, 2010; van der Zouwen et al, 2018). Research has demonstrated that maternal warmth may interrupt the development of affective psychopathic traits in youth (Kimonis et al, 2013; Waller et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…There has been a focus on studies using incarcerated populations, through the study of psychopathic scores (Bisby et al, 2017;Frodi et al, 2001) and an increase in studies conducted with non-clinical populations (e.g., Blanchard & Lyons, 2016;Mack et al, 2011), yet the results are far from conclusive. While there is support for both avoidance and anxiety attachment being associated with higher psychopathy scores in a non-clinical population (Mack et al, 2011), Van Der Zouwen et al (2018) found no significant results in community samples compared to clinical samples. Given these mixed findings, this study aims to look more into community samples and examine the significance of this association.…”
mentioning
confidence: 80%
“…This finding is in-line with previous research (e.g., Blanchard & Lyons, 2016;Walsh et al, 2019) and is supported by the attachment framework (Brennan et al, 1998) considering that attachment avoidance involves fear of depending on others within interpersonal relationships, with an excessive need for self-reliance. Thus, individuals with high levels of avoidance attachment, tend to evade intimate and close relationships, use deactivating strategies that minimize the experience of rejection to protect against threats of selfimage (Fraley & Shaver, 1997;Mikulincer & Shaver, 2007), which limits their access and awareness of recognizing emotions in others making it difficult for them to empathize, key characteristics of CU traits (i.e., Henschel et al, 2020;Mack et al, 2011;Mikulincer & Shaver, 2007;Simpson et al, 2011;Van Der Zouwen et al, 2018). Taking the aforementioned findings into account, in combination with an established link between empathetic and moral disturbances with the affectiveinterpersonal features of psychopathy in both genders (Seara-Cardoso et al, 2012), it seems that attachment avoidance should be prioritized when designing interventions for individuals with CU traits within clinical settings (Daly & Mallinckrodt, 2009) in managing CU traits but also in mainstream settings (schools, parenting programs) focusing on prevention (Kyranides et al, 2018;Rose et al, 2019).…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 99%
See 2 more Smart Citations